(untitled) (Biodiversitas Journal of Biological Diversity, 2017)
Suryawan A, Yuliantoro I, Mayasari A, Christita M. 2016. Identification of Aves, Herpetofauna and Arthropods in Miangas Island (Indonesia), the borderline of Wallacea ecoregion. Biodiversitas 18: 1528-1537. Miangas Island is located on the northeast of Wallacea and bordered by the Philippines and it belongs to Talaud archipelago. This study aims to identify the species of terrestrial wildlife in Miangas Island. Observations used the direct encounter method starting at 7:00 to 17:00 pm and they were conducted through four times visits in October and December 2015, April and May 2016. Some species were found, such as 15 species of birds, 3 species of lizards, 1 snake and 1 species of Arthropods. Hirundapus caudacutus and Butastur indicus are migrant bird species. Lamprolepis smaragdina is green and classified as tree climber type. It is included to hybrid lizard type of the Pacific and the Philippines. Based on IUCN database, Eos histrio is classified as endangered group (E), Ducula pickeringii as vulnerable (V) Todirhamphus enigma enigma is classified as near threatened group (NT), Birgus latro is classified as Data deficient (DD), while Butastur indicus, Lanius Schach, Nectarinia jugular plateni, Todirhamphus chloris, Hirundo tahitica, Hirundapus caudacutus, Egretta sacra, Ardea alba, Anthus cervinus, Motacilla cinerea, Cuculus saturatus, Passer Montanus, Ducula pickeringii, Eutropis multicarinata multicarinata, Lamprolepis smaragdina, Emoia caeruleocauda and Laticauda laticauda are classified as low risk (LC).